Materials processing technology with Islamic perspective - Maleque, Md. Abdul (2017)
Human being is the best creation of Allah (swt) on the earth. Any knowledge that possesses human being is actually from the divine source. Therefore, the knowledge of materials processing technology given by Allah (swt) is for the betterment of the human life of the entire world. Historically, materials processing technology is not new rather old since started from ancient time as mentioned it in the Holy Qur’an. The existence of iron and other metals in the earth crust, atomic structure of the materials, melting of them for the processing purposes, joining of material etc. have also been highlighted in the Holy Book. Powder metallurgy process technology as one of the materials processing technologies has been discussed in this article in terms of atomization, compaction and sintering in order to understand the materials processing technology with Islamic perspective. It can be said that though a great advancement of the world in the area of technology has been done but one should realize that everything comes from Allah, the Creator of Man and Earth.